Evaluación de la biostimulación del floc bacteriano presente en suelos acuícolas de baja salinidad para tratamiento de materia orgánica. - Ramirez Loaiza, Justin Rodrigo; Ramírez Solano, Kevin Maximo (Machala : Universidad Técnica de Machala, 2023)
High aquaculture production leads to the accumulation of sediments and organic matter on the bottom, resulting in toxic nitrogen compounds and harmful microorganisms such as Vibrio. Biostimulants and biosurfactants have been developed to address this problem. Biostimulation, which is less intrusive, uses native microorganisms such as Bacillus to control organic matter in low salinity environments. Products that provide nutrients and carbon are needed to increase bacterial biomass and facilitate bioremediation. This research biostimulates bacterial floc in low salinity aquaculture soils through the application of nutrients, measuring the effectiveness of native bacteria found in the sediment, as an alternative to commercial products, whose effectiveness is not always guaranteed in all aquaculture production scenarios. In a completely randomized experiment consisting of 12 plastic trays, three different treatments (SiCa, Molasses and SiCa + Molasses) and a control treatment (0) to which nothing was applied. The experiment lasted for 28 days; to determine the load of Bacillus and Vibrio after biostimulation, it was determined by seeding in plates of successive dilutions, and to determine the load of organic matter obtained after biostimulation of the bacterial floc, the Walkley & Black method was used. This experiment is completely randomized, consisting of 12 plastic trays and three different treatments (SiCa, Molasses and SiCa + Molasses), including a control treatment (0) to which nothing was applied. The experiment lasted for 28 days; to determine the load of Bacillus spp. and Vibrio sp. after biostimulation was determined by plate seeding with successive dilutions and to determine the load of organic matter obtained after biostimulation of the bacterial floc, the Walkley & Black method was used. The results obtained from the experiment were able to determine a significant difference between the different treatments, with treatment 3 (SiCa + Molasses) showing a higher Bacillus load with respect to the control treatment and a reduction in the Vibrio load, in addition to showing a considerable reduction in the organic matter present, since from 4.25%, treatment 3 achieved a value of 0.23%. In conclusion, biostimulation can be used to biostimulate the native bacterial floc in aquaculture soils of low salinity for the treatment of organic matter.
La alta producción acuícola genera acumulación de sedimentos y materia orgánica en los fondos, propiciando compuestos nitrogenados tóxicos y microorganismos perjudiciales como el Vibrio. Para abordar este problema, se han desarrollado bioestimuladores y bioaumentadores. La bioestimulación, menos intrusiva, aprovecha microorganismos nativos como el Bacillus para controlar la materia orgánica en entornos de baja salinidad. Se requieren productos que proporcionen nutrientes y carbono para aumentar la biomasa bacteriana y facilitar la biorremediación. Esta investigación bioestimula el floc bacteriano en suelos acuícolas de baja salinidad mediante la aplicación de nutrientes, midiendo la efectividad de las bacterias nativas que se encuentran en el sedimento, como alternativa a productos comerciales, cuya eficacia no siempre está garantizada en todos los escenarios de producción acuícola. Este experimento es completamente al azar conformado por 12 bandejas plásticas y tres diferentes tratamientos (SiCa, Melaza y SiCa + Melaza), con un tratamiento control (0) al que no se le aplicaba nada. El experimento tuvo una duración de 28 días, para determinar la carga de Bacillus spp. y Vibrio sp., después de la bioestimulación se determinó mediante siembra en placa con diluciones sucesivas y para determinar la carga de materia orgánica obtenida después de haber bioestimulado el floc bacteriano se usó el método de Walkley & Black. Los resultados obtenidos del experimento, lograron determinar una diferencia significativas entre los diferentes tratamientos siendo el tratamiento 3 (SiCa + Melaza) que presento una mayor carga de Bacillus con respecto al tratamiento control y una reducción a la carga de Vibrio, además que logro evidenciar una reducción considerable de la materia orgánica presente ya que de 4,25% el Tratamiento 3 logro obtener un valor de 0,23%. Concluyendo que la bioestimulación puede ser usada para bioestimular el floc bacteriano nativo en suelos acuícola de baja salinidad para el tratamiento de materia orgánica.
Keywords: ACUICULTURA; BIOESTIMULACION; BACILLUS; VIBRIO Y MATERIA ORGANICA